The Distribution of Police Protection - Thacher, David (Journal of quantitative criminology, 2011)
This paper investigates the distribution of police protection in the United States by race and class. By examining police employment and demographic data for every general-service police jurisdiction in the US, I find that poor and heavily-nonwhite jurisdictions employ far fewer officers per crime than wealthy and white jurisdictions do. That finding contrasts with an older body of literature on the distribution of police protection, which examined the distribution of police resources across neighborhoods within individual cities and found little inequality. I also find that inequality in police protection has grown since 1970—a finding that contrasts with the increasingly equal distribution of resources for education, the other major claim on local government revenues—largely because criminal victimization became more concentrated in disadvantaged communities. (In the process, I find that contrary to widespread impressions, the crime rate fell very little in the most disadvantaged jurisdictions from 1980 to 2000, and violent crime actually increased). Finally, by examining data about federal grant programs, I find that the rise of federal contributions to local policing in the 1990s slowed the growth of inequality somewhat, suggesting that revenue-sharing has a real but modest role to play in reducing inequality in police protection. Together these findings highlight a neglected aspect of equality in criminal justice.